2011 Atlanta Conference on Science and Innovation Policy 2011
DOI: 10.1109/acsip.2011.6064465
|View full text |Cite
|
Sign up to set email alerts
|

Effects of innovation on employment in Latin America

Abstract: Abstract-This study examines the impact of process and product innovation on employment growth across four Latin American countries (Argentina, Chile, Costa Rica, and Uruguay) using micro data from innovation surveys. Specifically, we relate employment growth to process innovations and to the growth of sales separately due to innovative and unchanged products. Results show that that compensation effects are prevalent, and the introduction of new products is associated with employment growth at the firm level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 15 publications
6
49
0
10
Order By: Relevance
“…First, we consider firm size (logSize). Previous studies about innovation in Latin America stressed that the relatively small size of the firms can affect access to the minimum financial and human resources needed to conduct disembodied TI activities (Crespi and Tacsir, 2012;Chudnovsky et al, 2006). Therefore, we expect a positive relationship between the firm's size and TI propensity.…”
Section: Control Variablesmentioning
confidence: 75%
See 1 more Smart Citation
“…First, we consider firm size (logSize). Previous studies about innovation in Latin America stressed that the relatively small size of the firms can affect access to the minimum financial and human resources needed to conduct disembodied TI activities (Crespi and Tacsir, 2012;Chudnovsky et al, 2006). Therefore, we expect a positive relationship between the firm's size and TI propensity.…”
Section: Control Variablesmentioning
confidence: 75%
“…Empirical evidence stresses that firms that conduct TI are usually engaged in a TI strategy that includes acquiring embodied knowledge (Crespi and Tacsir, 2012;Evangelista et al, 1997), although this does not imply a trend in the other direction from embodied to disembodied TI. Therefore, the second dependent variable (embodied) takes a value of 1 for all the firms that conducted any disembodied TI, regardless of whether they also carried out embodied TI.…”
Section: Dependent Variable: Technological Innovation (Disembodied Vsmentioning
confidence: 99%
“…Cabe señalar que hay escasa diferencia entre los efectos marginales de las variables que miden innovación de productos e innovación de procesos, a pesar de que la literatura afirma que estas pueden tener distintos efectos sobre la demanda de habilidades y sobre el empleo. Por ejemplo, evidencia reciente para ALC muestra que la innovación de productos puede ser más complementaria al trabajo calificado que al trabajo no calificado (Crespi y Tacsir, 2012). Otro factor que puede estar relacionado con el complejo vínculo entre innovación y productividad es el acceso y uso de TIC, aunque la relación no es tan sencilla ni lineal como se podría esperar.…”
Section: Efectos Marginalesunclassified
“…Interestingly, we find no difference in the marginal effects of the variables that measure innovations in products versus innovations in processes, even though the literature has stated that these may have differential effects on skill demand and on employment. Recent evidence for LAC has shown that product innovation may be more complementary to skilled than to unskilled labor (Crespi and E. Tacsir 2012).…”
Section: Determinants Of Ojt In Lacmentioning
confidence: 99%